Diet quality assessment indexes - Carvalho, Kênia Mara Baiocchi de (2014)
Various indices and scores based on admittedly healthy dietary patterns or food guides for the general population, or aiming at the prevention of diet-related diseases have been developed to assess diet quality. The four indices preferred by most studies are: the Diet Quality Index; the Healthy Eating Index; the Mediterranean Diet Score; and the Overall Nutritional Quality Index. Other instruments based on these indices have been developed and the words 'adapted', 'revised', or 'new version I, II or III' added to their names. Even validated indices usually find only modest associations between diet and risk of disease or death, raising questions about their limitations and the complexity associated with measuring the causal relationship between diet and health parameters. The objective of this review is to describe the main instruments used for assessing diet quality, and the applications and limitations related to their use and interpretation.